2019
DOI: 10.25122/jml-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Pregnancy Related Weight Gain, Postpartum Weight loss and Obesity: a Prospective Study

Abstract: Weight gain during pregnancy can be a real risk factor for long-term obesity which has implications in all areas of medicine. This study is designed to assess pregnancy-related weight gain and postpartum weight loss, to identify a possible correlation between weight gain during pregnancy and the risk of obesity in the late postpartum period. The batch comprised 306 women, hospitalized in the Obstetrics and Gynecology Section of the “Nicolae Malaxa” Clinical Hospital between June - November 2017. During this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…In many developing countries, being married provides women with more excellent nancial stability, which in turn works as a protective factor from being underweight [56,57]. Other factors, such as using contraceptive pills, and weight gain in the postpartum phase, are more likely to be more prevalent among married women in many countries' contexts [56,57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many developing countries, being married provides women with more excellent nancial stability, which in turn works as a protective factor from being underweight [56,57]. Other factors, such as using contraceptive pills, and weight gain in the postpartum phase, are more likely to be more prevalent among married women in many countries' contexts [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…In many developing countries, being married provides women with more excellent nancial stability, which in turn works as a protective factor from being underweight [56,57]. Other factors, such as using contraceptive pills, and weight gain in the postpartum phase, are more likely to be more prevalent among married women in many countries' contexts [56,57]. One study in Ethiopia showed that women's nutritional status is affected by lactation, family planning method utilization, lack of education, illnesses, and poor dietary habits [58].…”
Section: Discussionmentioning
confidence: 99%
“… 46 Furthermore, women who have an obesogenic diet and may or may not be overweight in their first pregnancy, are more likely to present as obese in subsequent pregnancies. 47 , 48 , 49 One paper looking at the rates of poor pregnancy outcomes in first and second pregnancies stratified risks by change in BMI units between pregnancies, found that most poor outcomes (including preeclampsia, gestational diabetes, and LGA) increased with weight gain of just one or two BMI units between pregnancies, independent of if the mother was overweight or not. 50 Another study found that raised maternal BMI in a first pregnancy with uncomplicated outcome still increased the risk of poor outcome in the second pregnancy, even if these women have normal BMI in second pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal circumference was measured at the umbilicus using a tape measure (Nartea, Mitoiu & Nica 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The measurement was taken using ultrasound as the distance between the superficial part of the skin and the rectus abdominis muscle. • Abdominal circumference was measured at the umbilicus using a tape measure (Nartea, Mitoiu & Nica 2019). • Weight and height were measured using a telescopic height scale; these measurements were used to determine the BMI.…”
Section: Other Assessmentsmentioning
confidence: 99%